Clinical Robustness of Accelerated and Optimized Abdominal Diffusion-Weighted Imaging. Issue 10 (October 2017) - Taron, Jana; Weiß, Jakob; Martirosian, Petros; Seith, Ferdinand; Stemmer, Alto; Bamberg, Fabian; Notohamiprodjo, Mike
Abstract : Objectives: The aim of this study was to assess the robustness of an accelerated and optimized diffusion-weighted sequence in clinical routine abdominal imaging using the simultaneous multislice (SMS) technique for scan time reduction and 3-dimensional (3D) diagonal diffusion mode to optimize image quality. Materials and Methods: One hundred fifty consecutive patients received clinically indicated magnetic resonance imaging for abdominal imaging including an optimized SMS diffusion-weighted sequence (DWIOPT : diffusion mode 3D diagonal; SMS factor 2; scan time 1:44 minutes). A subgroup of 41 patients additionally received a standard diffusion-weighted sequence as reference (DWISTD : diffusion mode 4-scan trace; scan time 2:35 minutes). Qualitative and quantitative image parameters of DWISTD and DWIOPT were assessed and compared interindividually within the subgroup using dedicated statistics. Results: In all patients, image quality ratings in DWIOPT were rated very high (overall image quality, 4.6 [4–5]; contour sharpness of right/left hepatic lobe, 4.6 [4–5]/4.4 [4–5]; and lesion conspicuity, 4.5 [4.5–5]). Interindividually, DWIOPT proved superior to DWISTD in comparison of overall image quality (4.6 [4.6–4.7] vs 4.2 [4.1–4.2]; P = 0.025) and contour sharpness of the right/left hepatic lobe (4.6 [4.5–4.7]/4.3 [4.0–4.3] vs 4.3 [4.1–43]/4.0[3.0–4.0]; each P = 0.045); lesion conspicuity was comparable in DWIOPT and DWISTD (4.0 [4.8–5] vs 4.4 [4–5]; P = 0.461), and apparent diffusion coefficient (ADC) values showed no statistically significant difference (ADCOPT vs ADCSTD : right hepatic lobe, P = 0.084; kidney, P = 0.445). Interreader agreement was substantial with a kappa value of 0.78 ( P < 0.001). Conclusions: Diffusion-weighted imaging of the abdomen can be considerably accelerated and optimized integrating the SMS technique and a 3D diagonal diffusion mode. In a large patient cohort, this approach proved of superior image quality while maintaining similar ADC values compared with standard DWI. This technique seems applicable for daily clinical routine.